2009
DOI: 10.1056/nejmoa0903753
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Association Study of Leprosy

Abstract: BACKGROUND The narrow host range of Mycobacterium leprae and the fact that it is refractory to growth in culture has limited research on and the biologic understanding of leprosy. Host genetic factors are thought to influence susceptibility to infection as well as disease progression. METHODS We performed a two-stage genomewide association study by genotyping 706 patients and 1225 controls using the Human610-Quad BeadChip (Illumina). We then tested three independent replication sets for an association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
571
5
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 675 publications
(616 citation statements)
references
References 31 publications
23
571
5
9
Order By: Relevance
“…The sample sizes of the present TB GWAS were similar to those of other infectious diseases and it appears reasonable that one should be able to identify the common moderate-to highrisk polymorphisms that are present in other common infectious diseases, such as the association of human leukocyte antigen Class II with leprosy, 4 HbS is associated with malaria 5 and complement factor H variants are associated with meningococcal disease. 6 Failure in replication of top signals from the meta-analysis of GWASs of TB per se in Asian populations in the present study reinforce the results of GWASs in African TB; 7 no common polymorphisms with moderate to high risks to TB per se could be identified despite the ubiquitous nature of TB in global populations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The sample sizes of the present TB GWAS were similar to those of other infectious diseases and it appears reasonable that one should be able to identify the common moderate-to highrisk polymorphisms that are present in other common infectious diseases, such as the association of human leukocyte antigen Class II with leprosy, 4 HbS is associated with malaria 5 and complement factor H variants are associated with meningococcal disease. 6 Failure in replication of top signals from the meta-analysis of GWASs of TB per se in Asian populations in the present study reinforce the results of GWASs in African TB; 7 no common polymorphisms with moderate to high risks to TB per se could be identified despite the ubiquitous nature of TB in global populations.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, linkage analyses 1-3 and a genome-wide association study (GWAS) in leprosy 4 identified multiple genetic factors with moderate to large effect sizes in biologically relevant candidate genes, such as LTA, PARK2, HLA-DR-DQ, C13orf31, CCDC122 and RIPK2. For several common infectious diseases, susceptibility loci with moderate to large effect sizes (at-risk odds ratios 41.5) were successfully identified by GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…PARK2 is an E3 ubiquitinprotein ligase thought to regulate innate immunity. [15][16][17][18] NOD2 is an intracellular sensing molecule expressed by macrophages and epithelial cells that recognizes the bacterial cell-wall peptidoglycan and the muramyl dipeptides motif. It is, therefore, valid to hypothesize that PARK2 participates in ubiquination-mediated NOD2 signaling, whereas LRRK2, a leucine-rich repeat kinase 2, was shown to be a regulator of PARK2 activity.…”
Section: Host Genetics and Susceptibility To Leprosymentioning
confidence: 99%
“…It is, therefore, valid to hypothesize that PARK2 participates in ubiquination-mediated NOD2 signaling, whereas LRRK2, a leucine-rich repeat kinase 2, was shown to be a regulator of PARK2 activity. 17 SLC11A1 encodes an integral membrane protein expressed exclusively in cells of the immune system recruited to the membrane of a phagosome upon phagocytosis, a pathway likely to be involved in immune response to infectious diseases in general. 19 Only very recently attention has been paid to the genetic control of occurrence of type 1 and type 2 leprosy reactions that affect about 30-50% of leprosy patients and are considered the major causes of permanent neurological disability associated with the disease.…”
Section: Host Genetics and Susceptibility To Leprosymentioning
confidence: 99%
See 1 more Smart Citation